2014
DOI: 10.1111/ped.12201
|View full text |Cite
|
Sign up to set email alerts
|

Association of problem behavior with sleep problems and gastroesophageal reflux symptoms

Abstract: PB in adolescents are associated with sleep problems, including sleep bruxism, as well as lifestyle and food habits and GERD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
(123 reference statements)
0
3
0
4
Order By: Relevance
“…The other link could be the contents seen in Facebook which could induce depressive symptoms and anxiety which ended up with sleep disturbances [53]. Students who experienced daytime sleepiness are more likely to develop RBD symptoms, which is supported by another study [54]. This might be because daytime sleepiness disturbs circadian rhythm, which leads to the occurrence of RBD [55][56][57].…”
Section: Discussionmentioning
confidence: 82%
“…The other link could be the contents seen in Facebook which could induce depressive symptoms and anxiety which ended up with sleep disturbances [53]. Students who experienced daytime sleepiness are more likely to develop RBD symptoms, which is supported by another study [54]. This might be because daytime sleepiness disturbs circadian rhythm, which leads to the occurrence of RBD [55][56][57].…”
Section: Discussionmentioning
confidence: 82%
“…In a Greek study, unhealthy dietary habits such as skipping breakfast, fast‐food consumption, and consuming sweets were associated with inadequate sleep duration, but did not specifically address for SOL 34 . Another study revealed that children with problem behaviors were more likely to skip breakfast; however, difficulty falling asleep within 30 min was associated with problem behaviors rather than breakfast 35 . From the perspective of gene physiology, late sleep timing was associated with higher DNA methylation of several circadian genes, and circadian genes were related to breakfast pattern with eggs, milk, and refined grain in adolescents 36 .…”
Section: Discussionmentioning
confidence: 99%
“…34 Another study revealed that children with problem behaviors were more likely to skip breakfast; however, difficulty falling asleep within 30 min was associated with problem behaviors rather than breakfast. 35 From the perspective of gene physiology, late sleep timing was associated with higher DNA methylation of several circadian genes, and circadian genes were related to breakfast pattern with eggs, milk, and refined grain in adolescents. 36 The physiological mechanism underlying the association between SOL and breakfast has not yet been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, concluíram que, geralmente, essas crianças têm dificuldade de expressar seus sentimentos, passando facilmente por situações de aflição. Além do fator psicológico, tem se encontrado uma associação entre essa parafunção e alterações sistêmicas como o refluxo gastroesofágico, assim como, no estudo de Sakaguchi et al, 21 sendo o refluxo um fator de risco para o bruxismo noturno. Essa correlação é ancorada no aumento da atividade rítmica dos músculos da mastigação induzido pela acidificação esofágica proveniente do refluxo gastroesofágico.…”
unclassified
“…Essa correlação é ancorada no aumento da atividade rítmica dos músculos da mastigação induzido pela acidificação esofágica proveniente do refluxo gastroesofágico. 21,28 Dickman et al 29 sugerem que a qualidade do sono está relacionada com a gravidade do refluxo e que a insônia ocorre nos pacientes no dia seguinte à exposição ácida originária do refluxo gastroesofágico. 33 ao compararem a presença de apertamento dentário em crianças com paralisia cerebral e aquelas com ausência desse distúrbio, observou-se que a presença da parafunção é significativamente maior no primeiro grupo.…”
unclassified